Inducible cardiac arrhythmias caused by enhanced β(1)-adrenergic autoantibody expression in the rabbit - Li, Hongliang (American Physiological Society, 2013)
Previous studies demonstrated burst pacing and intravenous infusion of ACh induced sustained atrial tachycardia when rabbits were immunized to produce β(2)-adrenergic receptor (β(2)AR)-activating autoantibodies. The objective of this study was to examine the arrhythmogenic effect of β(1)-adrenergic receptor (β(1)AR)-activating autoantibodies in the rabbit. Eight New Zealand white rabbits were immunized with a β(1)AR second extracellular loop peptide to raise β(1)AR antibody titers. A catheter-based electrophysiological study was performed on anesthetized rabbits before and after immunization. Arrhythmia occurrence was determined in response to burst pacing before and after ACh infusion in incremental concentrations of 10 μM, 100 μM, and 1 mM. The baseline sinus heart rate before and after immunization averaged 149 ± 17 per min and 169 ± 16 per min, respectively (P < 0.05). In the preimmune studies, there were five sustained (≥10 s) arrhythmias in 32 induction attempts, which occurred in only four of eight rabbits. In the postimmune studies, there were 22 sustained arrhythmias in 32 induction attempts, which occurred in all eight rabbits (P < 0.0001 for the independent effect of immunization). Of the 22 sustained arrhythmias postimmunization, 15 were sinus tachycardia compared with only two before immunization (P < 0.01 for the independent effect of immunization). Postimmune (but not preimmune) rabbit sera demonstrated specific binding to β(1)AR and induced significant β(1)AR activation in transfected cells in vitro. No cross-reactivity with β(2)AR was observed. In conclusion, in contrast with rabbits with β(2)AR-activating autoantibodies that demonstrate predominantly atrial tachycardias, enhanced autoantibody activation of β(1)AR in the rabbit leads to tachyarrhythmias mainly in the form of sustained sinus tachycardia.